2017
DOI: 10.1002/1878-0261.12038
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of the miR‐194–CUL4B negative feedback loop drives tumorigenesis in non‐small‐cell lung carcinoma

Abstract: Cullin 4B (CUL4B), a scaffold protein that assembles CRL4B ubiquitin ligase complexes, is overexpressed in many types of cancers and represses many tumor suppressors through epigenetic mechanisms. However, the mechanisms by which CUL4B is upregulated remain to be elucidated. Here, we show that CUL4B is upregulated in non‐small‐cell lung carcinoma (NSCLC) tissues and is critically required for cell proliferation and migration in vitro and for xenograft tumor formation in vivo. We found that microRNA‐194 (miR‐19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 54 publications
(85 reference statements)
1
44
0
Order By: Relevance
“…Previous studies have indicated that some members of the Cullin protein family may be targeted by miRNAs (26,36). Moreover, CUL4B and miR-194 have been found to regulate each other directly in a coordinated manner (10). In the present study, we identified miR-381 and miR-489 as potential regulators of CUL4B using computational prediction tools.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Previous studies have indicated that some members of the Cullin protein family may be targeted by miRNAs (26,36). Moreover, CUL4B and miR-194 have been found to regulate each other directly in a coordinated manner (10). In the present study, we identified miR-381 and miR-489 as potential regulators of CUL4B using computational prediction tools.…”
Section: Discussionmentioning
confidence: 72%
“…Cullin 4B (CUL4B) is a scaffold protein responsible for assembling DDB1, RBX1 and substrate component to form the CRL4B ubiquitin ligase complexes (3), contributing to ubiquitin-mediated proteolysis and tumourigenesis (4,5). Mounting evidence has highlighted the upregulation and oncogenic potential of CUL4B in various types of cancer, including hepatocellular carcinoma, lung cancer, colon cancer and bladder cancer (6)(7)(8)(9)(10). Mechanistically, CUL4B epigenetically represses a series of tumour suppressors, including insulin-like growth factor-binding protein 3 (IGFBP3), phosphatase and tensin homolog (PTEN) and p16 through physical interaction with the SIN3A/HDAC and SUV39H1/HP1/DNMT3A complexes (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…As we alluded to above, emerging evidence had identified that CUL4B was highly expressed in different human malignancies, including carcinoma of the cervix, esophagus, liver, gastric and pancreatic cancer, and had a positive correlation with tumor progression [3,8,12,13,31]. Furthermore, CUL4B overexpression was significantly correlated with tumor size, advanced tumor stage, vascular and lymphatic invasion, distant metastasis, and histological differentiation, and was positively correlated with undesirable outcomes [3,[32][33][34].…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have demonstrated that CUL4B plays significant roles in the invasion, differentiation, and metastasis of carcinogenesis [11][12][13], the involved mechanisms may be related to signaling dysregulation. However, the expression and potential function of CUL4B in DLBCL is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…cells (22,23). Insulin-like growth factor 1 receptor (IGF1R) and Yes-associated protein 1 (YAP1) have been identified as targets of miR-194 by bioinformatics studies (24,25).…”
Section: Malat1 Knockdown Inhibits Hypopharyngeal Squamous Cell Carcimentioning
confidence: 99%